Mechanism of Hydraulic Fracturing Cutting Hard Basic Roof to Prevent Rockburst - Jianqiao Luo; Shaohong Yan; Tuo Yang; Haoqi Mu; Wensheng Wei; Yupeng Shen; Hongtao Mu (Shock and Vibration)
Rockburst is globally regarded as one of the most severe and complicated mining dynamic disasters to predict or control. Generally, the occurrence mechanism of rockbursts can be considered as a process of the elastic strain energy accumulation, emancipation, transmission, and occurrence. Tracing to the source, the reasons for large accumulation of elastic strain energy in coal and rock mass are the high stress of the roof layer that loads on the coal and rock masses around the mining space coupling effect with the natural horizontal tectonic stress. In this study, using the minimum energy theory and elasticity theory, the analytical formula for calculating elastic strain energy of the roof cantilever beam structure acting on the coal body load in front of the working face is deduced. Accordingly, we achieved a method of using hydraulic fracturing to improve the roof structure. In detail, we use a high-pressure jet to cut the cantilever roof structure, which can make a prelocated fracture surface, and then utilize the packers to make sure that the injected high-pressure fracturing fluid is propagating along the prelocated fracture surface and can cut off the cantilever roof structure eventually to prevent rockbursts in advance. Due to the rockburst occurrence mechanism and the quantitatively elastic strain energy analytical formula, a preconditioning water jet cutting induced fracture surface to create orientation-controllable hydraulic fracture strategy is proposed to guard against the high hazard caused by the massive elastic strain energy, which accumulated in the coal body in front of the working face and coal pillar.